Florfenicol and oxazolidone resistance status in livestock farms revealed by short- and long-read metagenomic sequencing - Yang, Xue; Zhang, Tiejun; Lei, Chang-Wei; Wang, Qin; Huang, Zheren; Chen, Xuan; Wang, Hong-Ning (Frontiers in Microbiology, 2022)
Antibiotic resistance genes (ARGs) as a new type of environmental contaminant pose a health risk to human. Intensive farms are recognized as hotspots for ARGs. Oxazolidinone is one of the most important antibiotics for the treatment of Gram-positive bacterial infections in humans. optrA, cfr, and poxtA are the key resistance genes that mediate co-resistance between florfenicol and oxazolidinone. Although oxazolidinones are not employed in the livestock industry, florfenicol is commonly used in farms to treat bacterial infections, which could help spread the cfr, optrA, and poxtA genes on farms. Genetic settings, hosts, and transferability of florfenicol and oxazolidinones resistance genes on chicken and swine farms in China are mostly unknown. Using metagenomics sequencing, we looked into the antibiotic resistome context of ten large-scale commercial farms in China. All of the samples had a high abundance and diversity of ARGs. The situation of florfenicol and oxazolidone resistance in pig farms is even more severe, which may be related to the excessive use of florfenicol in pig farms. Our findings provide evidence that there is a risk of co-transmission of florfenicol and oxazolidone resistance genes with other resistance genes. This study highlights that mobile genetic elements such as plasmids, ICEs, and transposons may facilitate the horizontal spread of floR, optrA and cfr. These findings expand our understanding of oxazolidone resistance in Chinese farms, implying that in order to stop the spread of oxazolidinone resistance genes, it is essential to use less florfenicol during breeding.